IMPACT OF MACROECONOMIC FACTORS ON THE BRICS STOCK EXCHANGE - Borodin, A.I; Panaedova, G.I; Kulagovskaya, T.A; Samoylik, E.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
There are many scientific studies on the role of stock markets and their impact on individual economies. However, the relationship between macroeconomic factors and the effectiveness of stock exchanges has not been fully studied by scientists. Analysis of the relationship can help predict volatility on stock exchanges, which is of great importance to investors and government entities alike. There is also no cross-country analysis of macroeconomic factors in BRICS countries. Within the framework of this article, the authors conducted an analysis of the impact of macroeconomic factors on the stock markets of BRICS countries. The dynamics of the S & P index, as well as the exchange rate, were found to be significant determinants for stock markets. Importantly, the impact of the exchange rate has been positive for commodity exporting countries (except Brazil, which has been a net importer since 2008) and negative for other countries. As a result of the study, the authors obtained the following well-founded results, namely, that BRICS countries were exposed to a similar set of factors, the scale of influence of individual factors being comparable; The exception is China 's stock market - for the latter, other factor estimates and much lower model quality were obtained; Key determinants of the BRICS stock market are US stock market dynamics, exchange rate, instant effect and selected monetary factors; For Russia, South Africa and Brazil, commodity prices have a positive impact on stock market dynamics; There is little impact of domestic non-monetary factors such as GDP or indices approximating GDP; Stock markets of all countries have very low error correction effects, i.e. do not seek a return to long-term equilibrium.